Pengaruh Penerapan Teaching Factory Untuk Meningkatkan Kompetensi Dan Jiwa Kewirausahaan Siswa SMKN 10 Luwu - Nadirah; Kamaruddin, Syamsu A. (Lembaga Pengembangan Kinerja Dosen, 2024)
In efforts to create strong entrepreneurs, the world of education, in this case vocational schools, is one of the institutions that has a very important role. Empirical facts show that the majority of vocational school graduates do not meet the needs or demands of stakeholders. Graduates tend to be